Pengembangan LKPD IPAS dengan Pendekatan Deep Learning Berbasis PBL untuk Meningkatkan Pemahaman Konsep Siswa pada Materi Cahaya di Kelas V SDN 59 Bengkulu Tengah - Wulan Nani; Endang Widi Winarni; Neza Agusdianita (UNIB Press, 2026)
This research aims to develop IPAS student worksheets with an in-depth learning based on PBL that are valid, practical, and effective in enhancing students conceptual understanding of light material in fifth grade at SDN 59 Bengkulu Tengah. This research employs a Reseach and Development (R &D) method using the ADDIE models, which consist of five stages: analysis, design, development, implication, and evaluation. The trial subjects were fifth grade students at SDN 59 Bengkulu Tengah, and fifth grade students at SDN 15 Bengkulu Tengah as effevtiveness test subjects, with a total 23 students. Research instruments included valiation sheets from content, language, and graphic design experts, observation sheets, teacher dan student response questinnaires, and conceptual understanding test. The research results indicaded that thedeveloped IPAS student worksheets meet the criteria of being valid, practical, and effective. The received “Highly feasible”assesments from content, language, and graphic design experts as well as “very good” responses from teacher dan students. The effectiveness also showed a significant improvement ins tudents conceptual understanding, with an average N-Gain 0f 0,5143 in the “Moderate” category for light material after using the student worksheets with an in- depth learning approach based on PBL. Thus the development of these IPAS student worksheets plays a crucial role in faciliting in-depth learning approach and enhancing the conceptual understanding on fifth grade students at SDN 59 Bengkulu Tengah.